Enhancement of taxane production in cell suspension culture of Corylus avellana L. Kalınkara by elicitation and precursor feeding - Ilayda Goktepe-Atilgan; Ahmet Dogan; Sule Ari (Biotechnology & Biotechnological Equipment)
Paclitaxel (trademark Taxol®) is the most effective chemotherapeutic agent against a wide range of cancers. Hazelnut (Corylus avellana L.) cell culture is a promising and inexpensive strategy for producing paclitaxel and related taxanes. This study evaluated the effect of elicitation and taxane precursor feeding for the enhancement of taxanes in a Turkish hazelnut (C. avellana cv. ‘Kalınkara’) cell suspension culture. Elicitor methyl jasmonate (100, 200 and 300 µmol L−1) and precursor phenylalanine (3μmol, 3 and 6 mmol L−1) were tested in cell suspension cultures. While methyl jasmonate increased the accumulation of taxanes, especially cephalomannine, via induction of the paclitaxel biosynthetic pathway, phenylalanine slightly induced the conversion of 10-deacetylbaccatin III and baccatin III to the end product paclitaxel (0.5349 µg g−1). The results showed that 200 µmol L−1 methyl jasmonate led to significantly greater induction of taxanes than 100 and 300 µmol L−1. The amount of cephalomannine (331.6 µg g−1) in cell suspension cultures elicited by 200 µmol L−1 methyl jasmonate was 8-fold higher than that in the control (41.61 µg g−1), while 10-deacetylbaccatin III (6.174 µg g−1) and baccatin III (3.956 µg g−1) increased almost twice as much as the control. The highest total paclitaxel yield was 5.453 µg g−1 in the same culture conditions. In conclusion, cell culture systems of C. avellana L. cv. ‘Kalınkara’ hazelnut, established for the first time, may become a potential candidate for industrial-level production of cephalomannine and other taxanes with further optimization.